Half-group of non-compact discrete subgroups relatively to operation of topological generation of subgroups - Супрун, О. М. (Proceedings of National Aviation University (archive), 1999)
The structure of compact cover nondiscrete topological Abel group in which family of subgroups is making a half-group of the operation of topological generation is studied. Nondiscrete topological Abel groups with half-group regarding the operation of topological generation family of descrete subgroups are described. The dual conditions are examined